Laporan Keuangan Sebagai Alat Pengukur Kinerja Keuangan - Rahmi Anugrah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2023)
Analysis of the financial statements at PT Astra International Tbk was conducted to measure the financial performance of the organization, in measuring this performance there are two methods, namely financial and non-financial aspects. In this study there is a standardization set to make something analyzed can be said to be feasible or not. This is done as a measuring tool to draw conclusions whether the company's performance can be said to be good or not. There for we need a measure for comparison. In this case, ratio analysis is used to see the company's capabilities, including the liquidity ratio and solvency ratio. This research uses a descriptive method with a qualitative approach in order to obtain information in this research obtained from secondary data sources and data collection from official websites and relevant reading studies from several sources. The final result of the research explains that the company as a whole is said to be able to fulfill all of its short-term obligations and the same with other company obligations.